Physiological Responses Manifested by Some Conventional Stress Parameters and Biophoton Emission in Winter Wheat as a Consequence of Cereal Leaf Beetle Infestation - Lukács, Helga; Jócsák, Ildikó; Somfalvi-Tóth, Katalin; Keszthelyi, Sándor (Frontiers in Plant Science, 2022)
Oulema melanopus L., (Coleoptera: Chrysomelidae) is one of the most serious pests of winter wheat and causes peeling of the epidermis and tissue loss. Since the complex mapping of the physiological responses triggered by O. melanopus, as a biotic stressor in winter wheat has not been fully explored with the help of non-invasive imaging and analytical assays, yet. The aim of the present work was to study the effect of O. melanopus on the physiological processes of winter wheat, especially on the extent of lipid peroxidation, and antioxidant activity derived from tissue destruction, as well as photosynthetic ability. The results of the measurements enabled the identification of the antioxidant and lipid oxidation–related physiological reactions and they were reflected in the dynamics of non-invasive biophoton emissions. Our non-invasive approach pointed out, that although in the case of O. melanopus infestation, the damage is manifested in tissue loss, the systemic signalling of the biotic stress may reached other plant parts as well, which was confirmed by the results of antioxidant capacity measurements. These results indicate that the plant react on the biotic stress on a whole organizational level. We identified that the antioxidant and lipid oxidation–related physiological reactions were reflected in the dynamics of two aspects of biophoton emission: delayed fluorescence and ultra-weak bioluminescence as well. Our research further supported that the non-invasive approach of stress assessment may complete and detail the traditional stress indicators.